Evaluating Abdominal and Lower-Back Muscle Activity While Performing Core Exercises on a Stability Ball and a Dynamic Office Chair. (November 2015) - Holmes, Michael W. R.; De Carvalho, Diana E.; Karakolis, Thomas; Callaghan, Jack P.
Objective: The purpose of this study was to evaluate the ability of a dynamic office chair to activate the core muscles while participants performed exercises sitting on the chair compared to a stability ball. Background: Prolonged sitting has become an accepted part of the modern office. However, epidemiological evidence suggests that sedentary postures are linked to many adverse effects on health. The concept of dynamic or active sitting is intended to promote movement while sitting to reduce the time spent in prolonged, static postures. Methods: Sixteen participants performed four pelvic rotation exercises (front-back, side-side, circular, and leg lift) on both a dynamic office chair and a stability ball. Muscle activity from 12 torso muscles were evaluated with surface electromyography. Results: For all exercises, trunk muscle activity on the chair was comparable to that on a stability ball. The right external oblique was the only muscle to produce greater peak activity ( p = .019) when using the ball compared to the chair (21.4 ± 14.0 percent maximal voluntary excitations (%MVE) and 14.7 ± 10.8 %MVE for the ball and chair, respectively). The left thoracic erector spinae produced greater average activity ( p = .044) on the chair than on the ball. Conclusion: These findings suggest that this dynamic sitting approach could be an effective tool for core muscle activation while promoting movement and exercise while sitting at work. Application: Muscle activations on the dynamic chair are comparable to those on a stability ball, and dynamic office chairs can promote movement and exercise while sitting at work.